Prevalence and Risk Factors of Work-Related Musculoskeletal Disorders Among Intensive Care Unit Nurses in China. (June 2019) - Yang, Shuai; Lu, Jingmei; Zeng, Jiaqi; Wang, Liqian; Li, Yinglan
This cross-sectional study investigated the prevalence and risk factors of work-related musculoskeletal disorders among intensive care nurses in the Hunan Province of China. Nurses working in mixed intensive care units of 20 tertiary hospitals in this province participated in an online survey regarding work-related musculoskeletal injuries. The seven-part questionnaire included basic demographics; job and workplace characteristics; risk perception; physical, psychosocial, and workplace organizational factors; and musculoskeletal symptoms. The response rate was 70.7% (702 of 993 nurses). Approximately 97% of the respondents reported experiencing at least one work-related musculoskeletal disorder within the previous year. Low back pain was the most commonly reported musculoskeletal disorder (80.1%), followed by neck (78.6%) and shoulder pain (70.4%). The multivariate logistic regression analysis indicated that work-related musculoskeletal disorders were significantly associated with female gender (odds ratio [OR] = 0.115), unmarried status (OR = 0.136), a greater perception of risk (OR = 2.352), and lack of a safe work environment (OR = 1.056). These findings underscore the need for nurses and managers to reinforce risk awareness, improve physical and psychosocial working conditions, and promote a safer work environment.